Poverty and Distributional Impact of Gas Price Hike in Armenia - Ersado, Lire (World Bank, Washington, DC, 2012)
Armenia meets about 75 percent of its energy needs through imports, with natural gas imports from Russia accounting for about 80 percent of total energy imports and 60 percent of total primary energy supply. Because of high dependence on imported energy, Armenia is vulnerable to external energy price shocks, which are often beyond the control of its policymakers. A most recent case in point was the 2010 Russian gas tariff increase, which led to a nearly 40 percent increase in the retail gas price for residential consumers. Coming on the heels of the global economic recession that hit Armenia's economy hard, the price hike amplified the impact on households that rely primarily on gas for heating and cooking. Using aggregate energy consumption data and a nationally representative household survey immediately before the crisis, this paper provides an overview of household energy consumption patterns, highlights Armenia's energy vulnerability, and estimates the direct poverty and distributional impacts of the increase in the cost of imported gas. The analysis shows that the gas price hike resulted in a significant increase in energy expenditures, with disproportionately higher impact on the poor and vulnerable households. The paper concludes with a discussion on the effectiveness of the mitigation measures employed by the Government of Armenia.